Intrinsic and scattering attenuation from borehole seismic and well log data - Alasbali, Abdulaziz Farraj (Curtin University, 2016)
Seismic attenuation is a major factor affecting seismic amplitudes. It is important to understand its spatial distribution in the overburden to correctly image seismic horizons and use qualitative interpretation techniques. Presence of free gas or overpressure in reservoir can significantly increase the attenuation. This study examines the magnitudes, mechanisms and spatial distribution of seismic attenuation from VSP and log data using wells in the North West shelf of Australia and the Middle East.